2022
DOI: 10.1108/ijm-04-2021-0261
|View full text |Cite
|
Sign up to set email alerts
|

Workplace ostracism and employee silence in service organizations: the moderating role of negative reciprocity beliefs

Abstract: PurposeEmployee silence is a pervasive workplace phenomenon that can cause severe economic losses to service organizations. Drawing on conservation of resource theory, the present research aims to investigate interpersonal antecedents of employee silence, specifically workplace ostracism while considering the moderating role of negative reciprocity beliefs (NRBs).Design/methodology/approachTwo-wave data collected from 355 employees working in service organizations in Pakistan supported the theorized model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 83 publications
2
27
0
Order By: Relevance
“…According to the authors, the sample size should be equal to or greater than “10 times the maximum number of arrow heads pointing at the latent endogenous variables,” or “10 times the largest number of the structural path” ( Hair et al, 2017 , p. 48). Several other well-cited studies employing SmartPLS SEM observed the minimum sample size of 207 to be appropriate for measuring the structural paths (e.g., Hassan and Ayub, 2019 ; Sahabuddin et al, 2021 ; Yao et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the authors, the sample size should be equal to or greater than “10 times the maximum number of arrow heads pointing at the latent endogenous variables,” or “10 times the largest number of the structural path” ( Hair et al, 2017 , p. 48). Several other well-cited studies employing SmartPLS SEM observed the minimum sample size of 207 to be appropriate for measuring the structural paths (e.g., Hassan and Ayub, 2019 ; Sahabuddin et al, 2021 ; Yao et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several well-recognized prior studies have utilized purposive sampling technique due to its ability to generate arbitrary responses. [52][53][54] Respondents mainly comprised managers, business people, civil servants and retirees, teachers, academics, and public and private sector employees. We distributed questionnaires along with a cover letter to the participants explaining the study's importance and guaranteeing the confidentiality of their responses.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Jahanzeb et al (2019) revealed that high levels of negative reciprocity make the negative linkage of abusive supervision with employee creativity via knowledge hiding strong. According to Yao et al (2022), negative reciprocity moderates the linkage of workplace ostracism with employee silence, making the associations more prominent among employees who have significant negative reciprocity. Based on these theoretical explanations and empirical evidence, we argue that employees' reciprocity beliefs moderate abusive supervision-psychological distress relationship.…”
Section: Moderated-mediation Effectmentioning
confidence: 99%